Characterization of Chromatin Structure-associated Histone Modifications in Breast Cancer Cells - Chang Pyo Hong; Moon Kyung Choe; Tae-Young Roh (Genomics & Informatics)
Chromatin structure and dynamics that are influenced by epigenetic marks, such as histone modification and DNA methylation, play a crucial role in modulating gene transcription. To understand the relationship between histone modifications and regulatory elements in breast cancer cells, we compared our chromatin immunoprecipitation sequencing (ChIP-Seq) histone modification patterns for histone H3K4me1, H3K4me3, H3K9/16ac, and H3K27me3 in MCF-7 cells with publicly available formaldehyde-assisted isolation of regulatory elements (FAIRE)-chip signals in human chromosomes 8, 11, and 12, identified by a method called FAIRE. Active regulatory elements defined by FAIRE were highly associated with active histone modifications, like H3K4me3 and H3K9/16ac, especially near transcription start sites. The H3K9/16ac-enriched genes that overlapped with FAIRE signals (FAIRE-H3K9/14ac) were moderately correlated with gene expression levels. We also identified functional sequence motifs at H3K4me1-enriched FAIRE sites upstream of putative promoters, suggesting that regulatory elements could be associated with H3K4me1 to be regarded as distal regulatory elements. Our results might provide an insight into epigenetic regulatory mechanisms explaining the association of histone modifications with open chromatin structure in breast cancer cells.